A clinical analysis of outcome in management of head injury in patients with highway road accidents - H., Kiran Shankar; ., Paparajamurthy; K., Mohan Kumar; K., Anand (International Journal of Research in Medical Sciences, 2017)
Background: Road traffic accidents (RTAs) are a major cause of misery, disability and death globally, with a disproportionate number occurring in developing countries. Complications from closed head injuries are the single largest cause of morbidity and mortality in patients who reach the hospital alive. The present study assesses the outcome in the management of head injury admitted in our hospital following RTA in the period of one year. Methods: This retrospective study carried out in the department of Neurosurgery in a rural tertiary hospital, Kolar, Karnataka, India. Patients who got admitted between periods of January 2012 to January 2013 were included in the study. All patients were clinically evaluated by a team comprising of doctors from surgical, medical and orthopedics specialties in the emergency department and subsequently admitted and treated at neurosurgery. The study was conducted based on these reports and observations and outcome of patients. The results were expressed as percentages. Results: At the time of admission 41% patients were under alcoholic influence, 97% patients had history of LOC, 50% patients had ENT bleed and 7.5% had CSF leak. The GCS score of less than 8 was seen in 33% cases, 9 to12 in 52% cases and between 12 to 14 in 15% patients. As per Glasgow outcome scale (GOS), 91% of patients had good recovery, 5.5% patients had disability (hemiparesis, ptosis) and 3.5% patients died in the course of treatment. Conclusions: Head injury due to RTA is a recognized major public health problem causing death and disability among the population. So it should be managed in time and also should be looked seriously by concerned authority for reducing the incidences of head injury associated with RTA and protecting people by debilitating conditions.